Bananas of Cook Islands: A catalog of banana diversity seen on the islands of Rarotonga and Aitutaki - Sachter-Smith, Gabriel L.; Sardos, J. (2021)
This is a catalog of banana diversity seen on the islands of Rarotonga and Aitutaki (Cook Islands) during the banana expedition organized from May, 20th to May, 21st 2019 by the Alliance of Bioversity International and CIAT, and the Ministry of Agriculture of the Cook Islands with support of the Pacific Community (SPC). The expedition was funded by the Crop Trust with contribution of CRP RTB.